Degradable biomedical magnesium alloy drug-eluting vascular stent and manufacturing method

JP2025505043APending Publication Date: 2025-02-19BEIJING AMSINO MEDICAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024547723
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2022-11-21
Publication Date
2025-02-19

AI Technical Summary

Benefits of technology

【0095】 本発明により提供される血管ステントは、冠動脈狭窄を模擬する大動物実験において良好な治療結果を示し、6カ月の経過観察において血管管腔に崩壊、炎症、内膜増殖がなく、分解過程において十分な安全性と有効性を示す。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505043000001_ABST
    Figure 2025505043000001_ABST
Patent Text Reader

Abstract

The present invention provides a degradable biomedical magnesium alloy drug-eluting vascular stent and a manufacturing method thereof. The magnesium alloy contains 3.0-6.0% by weight of Gd, 2.5-5.5% by weight of Y, 1.0-3.0% by weight of Li, 3-1.0% by weight of ZnO, 0.2-1.0% by weight of Zr, and the balance of Mg, with the total weight of the magnesium alloy being 100% by weight. The stent has good radial bearing strength and strain dispersion performance through finite element design. The corrosion resistance performance of the magnesium alloy stent using the protective coating layer is greatly improved. The composite drug sustained release system of arsenic trioxide or rapamycin and tacrolimus is used to fully adapt to the vascular damage repair process. The implantation results of large animals show that the vascular stent system has good anti-restenosis therapeutic effect.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the medical device field, specifically, the present invention relates to a degradable biomedical magnesium alloy, a vascular stent and a manufacturing method. [Background technology]

[0002] The use process of magnesium alloy vascular stents is a large deformation process. The stent must first be compressed and held by a balloon delivery system, and then pressurized and expanded after reaching the lesion site, and the local strain can reach 15% or more. Most surface treatments will result in localized damage after the stent is expanded. For example, when using poorly soluble magnesium salts such as magnesium fluoride, magnesium carbonate, magnesium phosphate, and hydroxyapatite, or magnesium oxide, magnesium hydroxide, etc. as the surface corrosion-resistant layer, even if a highly strong and dense surface corrosion-resistant layer is obtained by methods such as micro-arc oxidation, physical vapor deposition, chemical conversion, and electrochemical vapor deposition, the material of this corrosion-resistant layer is brittle, so that it will inevitably break or microcrack during the large deformation process, losing its local protective effect. The broken or cracked areas are usually areas of severe stress corrosion, which will rapidly reduce the supporting force of the stent.

[0003] Another method for improving the corrosion resistance of stents is to add a polymer coating layer to the surface of magnesium alloy stents. However, considering the characteristics of the large deformation process of stents, polymer materials with low elongation or low bonding strength with the substrate cannot meet the actual requirements. In addition, because the size of the stent is small and the structure is complicated, it is generally necessary to dissolve the polymer material in an organic solvent, apply it to the surface of the stent by spray coating or spin coating, and then volatilize the organic solvent to form a protective coating layer. Through the volatilization process of the organic solvent, fine pore passages are formed in the coating layer, and the magnesium alloy substrate can exchange ions with the external corrosive environment through the passages, which reduces the protective effect of the coating layer, and the corrosion progress is more pronounced, especially after the large deformation process, at the stress concentration points.

[0004] Rapid degradation of the stent also causes the local magnesium ion concentration to be too high, leading to inflammation and proliferation. Current vascular stent drugs and their release systems are generally designed for non-degradable stents or degradable stents that degrade particularly slowly (e.g., polylactic acid-based, pure iron-based, etc.), and are not suitable for magnesium alloy vascular stents that degrade relatively quickly. Summary of the Invention [Problem to be solved by the invention]

[0005] One object of the present invention is to provide a degradable magnesium alloy for biomedical use.

[0006] Another object of the present invention is to provide a degradable magnesium alloy drug-eluting vascular stent for biomedical use.

[0007] It is still another object of the present invention to provide a method for producing said degradable drug-eluting magnesium alloy vascular stent for biomedical use. [Means for solving the problem]

[0008] After undergoing a large deformation process under near-physiological conditions, the composite coating layer of the vascular stent of the present invention still has good protective effect on the stress concentration areas, and the unique composite drug release control system inhibits inflammation and proliferation at the implant site.

[0009] In order to achieve the above object, in one aspect, the present invention provides a degradable magnesium alloy for biomedical use, comprising 3.0-6.0 wt% Gd, 2.5-5.5 wt% Y, 1.0-3.0 wt% Li, 0.3-1.0 wt% Zn, 0.2-1.0 wt% Zr, and the balance Mg, with the total weight of the magnesium alloy being 100 wt%.

[0010] According to some specific embodiments of the present invention, the magnesium alloy has a tensile strength of 260-350 MPa, a yield strength of 160-280 MPa, and a breaking elongation of 10-28%.

[0011] The magnesium alloy of the present invention has good biocompatibility and uniform corrosion properties.

[0012] In another aspect, the present invention also provides a degradable magnesium alloy drug-eluting vascular stent for biomedical use, comprising a stent base 1, a polymer intermediate layer 7, a polymer protective layer 6, and a drug coating layer 8, which are arranged on the stent base from the inside to the outside, wherein the total weight of the stent base is taken as 100% by weight, and the material of the stent base 1 contains 3.0-6.0% by weight of Gd, 2.5-5.5% by weight of Y, 0.3-1.0% by weight of Zn, 0.2-1.0% by weight of Zr, and the remainder is Mg.

[0013] According to some specific embodiments of the present invention, the stent base 1 mainly comprises a plurality of annular supports 2, a connector 3 and an end developing structure 4, as shown in Figures 1 to 4, and each support 2 and the developing structure 4 are connected by a connector 3.

[0014] According to some specific embodiments of the present invention, any two adjacent supports 2 are mirror images of each other.

[0015] According to some specific embodiments of the present invention, the support 2 is mainly composed of support units 5, each support unit 5 consisting of one corrugated rod 51, two corrugated rod connecting sections 52 and one arc body 53, the corrugated rod connecting sections 52 are installed on both ends of the corrugated rod 51, the corrugated rod connecting section 52 at one end is connected to one end of both ends of the arc body 53 of the same support unit, and the corrugated rod connecting section 52 at the other end is connected to one end of the arc body 53 of an adjacent support unit (the other end of the arc body 53 of the same support unit is connected to the corrugated rod connecting section 52 of another support unit 5, that is, each support unit is connected head-to-tail), forming a ring-shaped support 2.

[0016] According to some specific embodiments of the present invention, the support 2 mainly consists of 4-18 support units 5 .

[0017] According to some specific embodiments of the present invention, the width of the corrugated rod 51 is 0.1mm-0.18mm. According to some specific embodiments of the present invention, the length of the corrugated rod 51 is 0.35mm-1.2mm. According to some specific embodiments of the present invention, the length of the corrugated rod 51 is 0.80mm-1.2mm.

[0018] According to some specific embodiments of the present invention, the width of the wavy rod connection section 52 is 0.01 mm-0.05 mm smaller than the width of the wavy rod 51 .

[0019] According to some specific embodiments of the present invention, the arc body 53 includes an outer arc 531 on the outside and an inner arc 532 on the inside, and the centers of the circles on which the inner arc 532 and the outer arc 531 are located are both located on the symmetry axis of the two wavy rods 51 connected to the same arc body 53, but are not concentric, and the center of the outer arc 531 is closer to the apex of the arc than the center of the inner arc 532, and the distance between the inner arc 532 and the outer arc 531 is smallest at the connection part with the wavy rod connection section 52, gradually increases toward the apex of the arc body 53, and is largest at the symmetry axis.

[0020] According to some specific embodiments of the present invention, the diameter of the outer arc 531 is 0.24-0.82 mm, the central angle is π / 2-3π / 2, the diameter of the inner arc 532 is 0.02-0.60 mm, the central angle is π / 2-3π / 2, and the distance between the center of the outer arc and the center of the inner arc is 0.01-0.05 mm.

[0021] According to some specific embodiments of the present invention, the diameter of the outer arc 531 is 0.40-0.80 mm, the central angle is π / 2-3π / 2, the diameter of the inner arc 532 is 0.20-0.45 mm, the central angle is π / 2-3π / 2, and the distance between the center of the outer arc and the center of the inner arc is 0.01-0.05 mm.

[0022] According to some specific embodiments of the present invention, the diameter of the outer circular arc 531 is greater than the diameter of the inner circular arc 532 .

[0023] According to some specific embodiments of the present invention, the maximum distance between the inner arc 532 and the outer arc 531 (i.e., the distance between the inner arc 532 and the outer arc 531 at the symmetrical axis) is 0.01 mm-0.05 mm larger than the width of the wavy rod, and the minimum distance (i.e., the distance between the inner arc 532 and the outer arc 531 at the two ends of the arc body 53) is 0.01 mm-0.05 mm smaller than the width of the wavy rod 51.

[0024] According to some specific embodiments of the present invention, the widths of both ends of the wavy rod connection section 52 are respectively the same as the width of the wavy rod 51 and the width of the end of the arc body 53 (i.e., the width of the connection part between the wavy rod connection section 52 and the wavy rod 51 is the same as the width of the wavy rod 51, and the width of the connection part between the wavy rod connection section 52 and the arc body 53 is the same as the width of the end of the arc body 53, thereby ensuring a smooth transition connection between the wavy rod connection section 52 and the wavy rod 51 and the arc body 53), and the intermediate width transitions gradually (i.e., the width of the wavy rod gradually decreases from the connection part with the wavy rod 51 to the connection part with the arc body 53).

[0025] The stent structure provided by the present invention has a unique design of non-concentric arc support unit 5, which makes the stress distribution of the entire stent structure uniform, makes it less likely to break during severe deformation processes such as compression, clamping and expansion, reduces stress corrosion, and improves the service life of the stent.

[0026] According to some specific embodiments of the present invention, the shape of the connector 3 is "C"-shaped, "I"-shaped or "S"-shaped.

[0027] According to some specific embodiments of the present invention, the developing structures are located at both ends of the stent substrate.

[0028] According to some specific embodiments of the present invention, the developing structure includes a developing point 41 and a developing structure body 42, and the developing structure body 42 has a developing hole 43 disposed therein.

[0029] According to some specific embodiments of the present invention, the diameter of the development spot 41 is 0.2mm-0.5mm, and the thickness is 0.1mm-0.2mm. According to some specific embodiments of the present invention, the diameter of the developing spot 41 is smaller than the diameter of the developing hole 43 by 0.005 mm-0.01 mm.

[0030] According to some specific embodiments of the present invention, each developing structure 4 is provided with one or two developing holes 43 .

[0031] To avoid the stent development being affected by the viewing angle, the stent development holes are generally not coaxial.

[0032] According to some specific embodiments of the present invention, the material of the development point 41 is one or a mixture of two or more selected from Pt, Au, and Pt / Ir alloy.

[0033] According to some specific embodiments of the present invention, the developing structure 4 is disposed between the two outermost supports at the end of the stent base (e.g., between the first and second supports at the left end).

[0034] According to some specific embodiments of the present invention, the connection 3 between two adjacent supports connected to the development structure 4 is an “I” type structure, and the connection 3 between any other two adjacent supports is a “C” type structure.

[0035] According to some specific embodiments of the present invention, the developing structure 4 and the first end support 2 (i.e., the outermost support) are connected by a trapezoidal connector 44, and the developing structure 4 and the second end support 2 are connected by an "I" type connector 45.

[0036] According to some specific embodiments of the present invention, the width of the two base sides of the trapezoidal connector 44 is 0.05-0.35 mm, respectively, and the difference between the widths of the two base sides is 0.02-0.08 mm.

[0037] According to some specific embodiments of the present invention, the long side (ie, the long base) of the trapezoidal connector 44 is connected to the support 2 , and the short side (ie, the short base) is connected to the developing structure 4 .

[0038] According to some specific embodiments of the present invention, the width of the "I" type connector is 0.05-0.18 mm.

[0039] The "I" type connector body is rectangular in shape, with natural chamfers formed at the connection points with the development structure and the support.

[0040] According to some specific embodiments of the invention, the stent has a compressed grip diameter of 0.8 mm-2.8 mm, an expanded diameter of 2.0 mm-8.0 mm, and a length of 6 mm-150 mm. According to some specific embodiments of the invention, the stent has a compressed grip diameter of 1.0 mm-2.0 mm, an expanded diameter of 2.2 mm-5.0 mm, and a length of 10 mm-50 mm. According to some specific embodiments of the invention, the stent has a compressed grip diameter of 1.0 mm-1.5 mm, an expanded diameter of 2.5 mm-3.5 mm, and a length of 10 mm-20 mm.

[0041] According to some specific embodiments of the present invention, the vascular stent further includes a polymer protective layer 6 disposed on the surface of the stent base 1, as shown in FIG. 5, the polymer in the polymer protective layer is polyvinylidene fluoride and its copolymer (polyvinylidene fluoride-hexafluoropropylene copolymer), and the thickness of the polymer protective layer 6 is 2 μm-10 μm.

[0042] According to some specific embodiments of the present invention, the thickness of the polymeric protective layer 6 is 4 μm-8 μm. According to some specific embodiments of the present invention, the thickness of the polymeric protective layer 6 is 5 μm-6 μm.

[0043] According to some specific embodiments of the present invention, the polymeric protective layer 6 is annealed to reduce its porosity.

[0044] The polymer protective layer 6 of the present invention has good biocompatibility, and with an elongation rate of 100-300%, it can meet the requirement of large deformation of the stent. With an extremely low water absorption rate of 0.01-0.05%, it can effectively block contact between the magnesium alloy substrate and bodily fluids or blood that have infiltrated through the micropores or broken parts of the stent drug release control coating layer, reduce ion exchange, and improve the corrosion resistance of the magnesium alloy stent.

[0045] According to some specific embodiments of the present invention, the vascular stent further includes a polymer intermediate layer 7 disposed between the stent base 1 and the polymer protective layer 6, as shown in FIG. 5, the polymer in the polymer intermediate layer is one or a combination of polyvinylidene fluoride and its copolymer (polyvinylidene fluoride-hexafluoropropylene copolymer), polymethyl methacrylate, and polybutyl methacrylate, and the thickness of the polymer intermediate layer is 100 nm-2000 nm.

[0046] According to some specific embodiments of the present invention, the thickness of the polymer interlayer is 500 nm-1500 nm. According to some specific embodiments of the present invention, the thickness of the polymer interlayer is 800 nm-1200 nm. According to some specific embodiments of the present invention, the thickness of the polymer interlayer is 800 nm-1000 nm.

[0047] The polymer intermediate layer acts as a binder to improve the fastness of the polymer protective layer, and also to block bodily fluids or blood that may penetrate through the micropore passages or uncovered areas of the polymer protective layer.

[0048] According to some specific embodiments of the present invention, the polymer interlayer 7 is a magnesium fluoride sealed polymer interlayer.

[0049] The sealing treatment with magnesium fluoride refers to a fluoridation treatment of a magnesium alloy stent coated with a polymer intermediate layer.

[0050] The fluorination treatment forms a magnesium fluoride barrier in the micropores or uncovered areas of the magnesium alloy stent substrate (magnesium alloy substrate) and the polymer interlayer, further blocking contact between the magnesium alloy stent substrate and body fluids or blood and reducing the occurrence of localized corrosion.

[0051] According to some specific embodiments of the present invention, the vascular stent further includes a drug coating layer 8 disposed on the outer surface of the polymer protective layer 6, as shown in FIG. 5, and the components of the drug coating layer include a polymer carrier and an active drug, and the active drug is a combination of tacrolimus and one selected from rapamycin and diarsenic trioxide (i.e., a combination of tacrolimus and rapamycin, or a combination of tacrolimus and diarsenic trioxide).

[0052] According to some specific embodiments of the present invention, the polymeric material of the polymeric carrier is one or a combination of one or more selected from polylactic acid, racemic polylactic acid, polyglycolic acid, polylactic-glycolic acid, polycaprolactone, and polyhydroxybutyric acid-hydroxyvaleric acid copolyester.

[0053] According to some specific embodiments of the present invention, the weight ratio of the polymeric carrier to the active drug is 2:1-10:1. According to some specific embodiments of the present invention, the weight ratio of the polymeric carrier to the active drug is 4:1-8:1. According to some specific embodiments of the present invention, the weight ratio of the polymeric carrier to the active drug is 5:1-7:1.

[0054] According to some specific embodiments of the present invention, the weight ratio of arsenic trioxide or rapamycin to tacrolimus is 1:2-4:1. According to some specific embodiments of the present invention, the weight ratio of arsenic trioxide or rapamycin to tacrolimus is 1:1-3:1.

[0055] According to some specific embodiments of the present invention, the content of arsenic trioxide or rapamycin in the drug coating layer 8 is 2-20 μg / mm, and the content of tacrolimus drug is 1-25 μg / mm. According to some specific embodiments of the present invention, the content of arsenic trioxide or rapamycin in the drug coating layer 8 is 5-15 μg / mm, and the content of tacrolimus drug is 1-6 μg / mm.

[0056] According to some specific embodiments of the present invention, the content of arsenic trioxide or rapamycin in the drug coating layer 8 is 5-10 μg / mm, and the content of tacrolimus drug is 2-5 μg / mm.

[0057] In a further aspect, the present invention provides a method for producing the degradable biomedical magnesium alloy drug-eluting vascular stent, comprising the steps of: (1) Processing of the stent base body 1 (2) Coating of polymer intermediate layer 7 (3) Coating of polymer protective layer 6 (4) Application of drug coating layer 8

[0058] According to some specific embodiments of the present invention, step (1), processing of the stent substrate, comprises the following steps. (11) Manufacturing the degradable biomedical magnesium alloy into a magnesium alloy pipe by a material forming process. (12) manufacturing the magnesium alloy tube into a cut stent by a laser engraving process. (13) A process for removing cutting residues and oxide layers by ultrasonic cleaning. (14) Obtaining a magnesium alloy stent substrate with a clean and flat surface through an electrochemical polishing process.

[0059] According to some specific embodiments of the present invention, the material forming process in step (11) includes producing a magnesium alloy ingot with the components and weight ratio of the degradable biomedical magnesium alloy by a vacuum semi-continuous casting method, subjecting it to solution treatment and then extruding it to produce a magnesium alloy bar, and further producing a magnesium alloy tube by a tube drawing process.

[0060] According to some specific embodiments of the present invention, the magnesium alloy tube has an outer diameter of 1.4-4.0 mm, a wall thickness of 0.08-0.30 mm, and a length of 0.5-2.0 m.

[0061] The size of the magnesium alloy tube can be adjusted according to the expanded outer diameter of the magnesium alloy stent and the requirements of the laser engraving equipment.

[0062] According to some specific embodiments of the present invention, the ultrasonic cleaning in step (13) includes immersing the cut stent obtained in step (12) in a cleaning solution for magnesium alloy stent and ultrasonicating for 1 to 8 minutes to remove cutting residues and oxide layer formed by laser engraving and attached to the surface.

[0063] According to some specific embodiments of the present invention, the cleaning solution for the magnesium alloy stent is prepared by potassium dihydrogen phosphate, potassium fluoride, absolute ethanol and purified water.

[0064] According to some specific embodiments of the present invention, in the magnesium alloy stent cleaning solution, the content of each component per unit volume of the magnesium alloy stent cleaning solution is 30-50g / L potassium dihydrogen phosphate, 15-25g / L potassium fluoride, and 150-250ml / L absolute ethanol, and preferably 40g / L potassium dihydrogen phosphate, 20g / L potassium fluoride, and 200ml / L absolute ethanol.

[0065] According to some specific embodiments of the present invention, the electrochemical polishing process in step (14) includes immersing the cut stent after cleaning into a polishing solution for magnesium alloy stent to perform electrochemical polishing, the polishing temperature is 18-60°C, the polishing current is 0.3-1.5A, and the polishing time is 10-500s.

[0066] According to some specific embodiments of the present invention, the polishing solution for the magnesium alloy stent is prepared by mixing phosphoric acid, anhydrous ethanol and purified water in a volume ratio of (0.8-1.2):(0.8-1.2):(0.8-1.2), and preferably, the volume ratio is 1:1:1.

[0067] According to some specific embodiments of the present invention, step (2), applying the polymeric interlayer, comprises the following steps: (21) applying a polymeric intermediate layer to the surface of the stent substrate; (22) A step of fluorinating the stent having the polymer intermediate layer applied thereon.

[0068] According to some specific embodiments of the present invention, step (21) includes forming a polymeric intermediate layer on the surface of the stent substrate by an ultrasonic spray coating process.

[0069] According to some specific embodiments of the present invention, the fluorination treatment includes immersing the stent substrate having the polymer intermediate layer applied thereto in a fluorination treatment solution to perform a fluorination sealing treatment on the polymer intermediate layer.

[0070] According to some specific embodiments of the present invention, the fluorination treatment includes immersing the stent substrate coated with the polymer intermediate layer in a fluorination treatment solution and continuously stirring the solution in a water bath shaker at a rotation speed of 50 to 200 r / min to fluorinate-seal the polymer intermediate layer.

[0071] According to some specific embodiments of the present invention, the fluoridation treatment solution is prepared from a hydrofluoric acid solution and a potassium fluoride solution.

[0072] According to some specific embodiments of the present invention, the concentration of the hydrofluoric acid solution is 10-40% (volume concentration), the concentration of the potassium fluoride solution is 0.5-5 mol / L, and the volume ratio of the hydrofluoric acid solution to the potassium fluoride solution is 100:5-100:50. According to some specific embodiments of the present invention, the temperature of the fluorination treatment solution is 18-85° C., and the treatment time is 30-600 min.

[0073] According to some specific embodiments of the present invention, step (3), applying the polymeric protective layer, comprises the following steps: (31) Step of applying a polymer protective layer (32) Annealing the stent with the polymeric protective layer applied thereto.

[0074] According to some specific embodiments of the present invention, step (31) includes forming a polymeric protective layer on the surface of the fluorinated polymeric interlayer by an ultrasonic spray coating process.

[0075] According to some specific embodiments of the present invention, the annealing treatment in step (32) includes heating the stent coated with the polymer protective layer to 60-200°C under vacuum condition, keeping the temperature for 1-10 h, and then cooling to room temperature and removing the stent.

[0076] According to some specific embodiments of the present invention, the annealing temperature is 100-150°C, preferably 120-130°C.

[0077] According to some specific embodiments of the present invention, the annealing time is 2-8 h.

[0078] According to some specific embodiments of the present invention, the annealing step includes placing the stent with the polymeric protective layer applied thereto in a quartz dish and annealing the stent.

[0079] According to some specific embodiments of the present invention, the vacuum degree of the vacuum condition is 1×10 -3Pa or more.

[0080] According to some specific embodiments of the present invention, the annealing treatment includes naturally cooling to below 50° C., introducing argon gas, and subsequently cooling to room temperature before removing the stent.

[0081] According to some specific embodiments of the present invention, step (4) includes forming a drug coating layer on the surface of the stent protective coating layer by an ultrasonic spray coating process.

[0082] According to some specific embodiments of the present invention, the ultrasonic spray coating process in step (21), step (31) and step (4) is to dissolve the material raw material (polymer or a mixture of polymer carrier and active drug) of each layer to be spray coated in each step in a volatile organic solvent, atomize it by ultrasonic wave, and then spray coat it on the surface of the stent or the adjacent lining layer (polymer intermediate layer or polymer protective layer), and form the corresponding layer structure (polymer intermediate layer, polymer protective layer or drug coating layer) after volatilizing the organic solvent.

[0083] According to some specific embodiments of the invention, the method comprises the steps of: (a) manufacturing said degradable biomedical magnesium alloy into a magnesium alloy tube by a material forming process; (b) fabricating the magnesium alloy tube into a cut stent by a laser engraving process. (c) A process for removing cutting residues and oxide layers by ultrasonic cleaning. (d) obtaining a magnesium alloy stent substrate with a clean and flat surface by electrochemical polishing process; (e) forming a polymer interlayer on the surface of the magnesium alloy stent substrate by an ultrasonic spray coating process; (f) treating the magnesium alloy stent having the polymer interlayer coated on its surface by a fluorination process. (g) forming a polymeric protective layer on the surface of the fluorinated polymeric interlayer by an ultrasonic spray coating process; (h) sealing the stent protective coating layer by annealing (i) forming a drug coating layer on the surface of the stent protective coating layer by an ultrasonic spray coating process; (j) obtaining a degradable biomedical magnesium alloy drug-eluting vascular stent after drying.

[0084] In a further aspect, the present invention provides an application of said degradable biomedical magnesium alloy drug-eluting vascular stent in manufacturing a medical device for treating vascular stenosis.

[0085] In a further aspect, the present invention provides a method for evaluating a degradable biomedical magnesium alloy drug-eluting vascular stent in an animal model of vascular stenosis, comprising: first, pretreating the animal model to form a vascular embolism model, and then implanting the degradable biomedical magnesium alloy drug-eluting vascular stent provided by the present invention; and then, at different time points after surgery, observing the stent by angiography and intravascular OCT, and comprehensively evaluating the degree of intimal coverage, restenosis and degradation status of the stent.

[0086] According to some specific embodiments of the present invention, the pretreatment of the animal model involves dilating the blood vessel at the vascular position where the stent is to be implanted at an expansion ratio of 1.3 to 1.5 times the diameter of the blood vessel using a disposable balloon dilation catheter, thereby damaging the blood vessel to a certain extent, and a vascular stenosis model can be formed 1 to 4 weeks after the pretreatment.

[0087] According to some specific embodiments of the present invention, the implantation refers to implanting the degradable biomedical magnesium alloy drug-eluting vascular stent provided by the present invention into a stenosis model with a stent expansion ratio of 1.1 to 1.3 times the vessel diameter.

[0088] As described above, the present invention provides a degradable magnesium alloy drug-eluting vascular stent for biomedical use and a manufacturing method thereof. The vascular stent of the present invention has the following advantages:

[0089] 1) The vascular stent substrate material provided by the present invention is a medical magnesium alloy material that can be absorbed by the human body, and has excellent properties such as high tensile strength, high elongation, high corrosion resistance and uniform decomposition.

[0090] 2) The vascular stent structure provided by the present invention is designed to effectively reduce the degree of stress concentration during stent expansion, and can be developed by X-ray.

[0091] 3) After the gap between the polymers of the vascular stent provided by the present invention is sealed with magnesium fluoride, a magnesium fluoride barrier can be formed in the micropores or uncoated areas of the stent coating layer, which further blocks the contact between the stent substrate and body fluids or blood, and effectively reduces the occurrence of local corrosion.

[0092] 4) The polymer protective layer of the vascular stent provided by the present invention has extremely high hydrophobicity, which can effectively block ion exchange between the stent and body fluids or blood, and improve the corrosion resistance of the stent.

[0093] 5) The annealing treatment method for the protective layer of a vascular stent provided by the present invention can effectively reduce the porosity, improve the bonding strength with the substrate, reduce the damage of the protective layer during large deformation of the stent, and further improve the corrosion resistance of the stent.

[0094] 6) The composite drug coating layer of the vascular stent provided by the present invention utilizes the characteristics of arsenic trioxide or rapamycin drugs to inhibit the growth of smooth muscle cells and promote the growth of endothelial cells, thereby achieving rapid endothelialization and effectively reducing the risk of thrombosis and the risk of stent decomposition and detachment; and utilizes the good anti-inflammatory effect of tacrolimus drug to effectively inhibit the inflammatory response occurring during the decomposition process of the stent, thereby reducing proliferation and in-stent restenosis.

[0095] The vascular stent provided by the present invention has shown good therapeutic results in large animal experiments simulating coronary artery stenosis, and in a six-month follow-up observation, there was no collapse, inflammation, or intimal proliferation in the vascular lumen, demonstrating sufficient safety and efficacy during the degradation process. [Brief description of the drawings]

[0096] [Figure 1] FIG. 1 is an overall schematic diagram of a degradable magnesium alloy drug-eluting vascular stent structure for biomedical use according to the present invention. [Diagram 2] FIG. 2 is an enlarged schematic view of a portion a in FIG. [Diagram 3] FIG. 2 is an enlarged schematic view of part b in FIG. [Figure 4] FIG. 2 is an enlarged schematic view of part c in FIG. [Diagram 5] FIG. 2 is a schematic diagram showing the structure of a composite coating layer of the degradable magnesium alloy drug-eluting vascular stent for biomedical use according to the present invention. [Figure 6] 1 is a pull-out curve of Test Example 1 of the present invention. [Figure 7] FIG. 2 is a corrosion potential diagram of Test Example 1 of the present invention. [Figure 8] FIG. 2 is a stress diagram of a normal vascular stent in Test Example 2 of the present invention. [Figure 9] FIG. 2 is a stress diagram of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 2 of the present invention. [Figure 10] FIG. 2 is a stress diagram of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 2 of the present invention. [Figure 11]FIG. 2 is an electron microscope image of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 3 of the present invention. [Figure 12] FIG. 2 is an electron microscope image of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 3 of the present invention. [Figure 13] FIG. 2 is an electron microscope image of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 3 of the present invention. [Figure 14] FIG. 2 is an electron microscope image of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 3 of the present invention. [Figure 15] FIG. 2 is an electron microscope image of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 3 of the present invention. [Figure 16] FIG. 2 is an electron microscope image of a comparative stent of Test Example 3 of the present invention. [Figure 17] FIG. 2 is an electron microscope image of a comparative stent of Test Example 3 of the present invention. [Figure 18] FIG. 13 is a graph showing the experimental results of the comparative stent in Test Example 4 of the present invention under near-physiological conditions. [Figure 19] FIG. 13 is a graph showing the experimental results of the comparative stent in Test Example 4 of the present invention under near-physiological conditions. [Figure 20] FIG. 13 is a graph showing the experimental results of the comparative stent in Test Example 4 of the present invention under near-physiological conditions. [Figure 21] FIG. 13 is a graph showing the experimental results of a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to Test Example 4 of the present invention. [Figure 22] FIG. 1 is an OCT image of Test Example 6 of the present invention. [Figure 23] FIG. 1 is an OCT image of Test Example 6 of the present invention. [Figure 24] FIG. 1 is an OCT image of Test Example 6 of the present invention. [Diagram 25] FIG. 1 is an OCT image of Test Example 6 of the present invention. [Figure 26] FIG. 1 is an OCT image of Test Example 6 of the present invention. [Figure 27] 1 is a photograph showing the developability of a stent in Test Example 6 of the present invention. [Figure 28]1 is a photograph showing the ultrasonic spray coating process of Example 4 of the stent of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0097] The technical solution of the present invention will be described in detail below with reference to the drawings and examples, but the protection scope of the present invention is not limited thereto.

[0098] Magnesium alloy material example 1 This embodiment provides a series of degradable biomedical magnesium alloy materials, the contents of their elemental components are shown in Table 1.

[0099] [Table 1]

[0100] The processing method includes the following: According to the compounding ratio of the content of each group of element components shown in Table 1, each alloy element was melted into a magnesium alloy ingot by vacuum semi-continuous casting, where the purity of each raw material component was 99.99%. The magnesium alloy ingot was solution treated, the solution temperature was 450°C, the solution time was 8 hours, and the magnesium alloy ingot was extruded into a rod with a diameter of 10 mm by hot extrusion, the hot extrusion temperature was 340°C. In order to avoid the influence of uneven mixing, 20% of the material length on both ends of the rod was cut, and only the middle part of the rod was used as the manufacturing material for the vascular stent.

[0101] Stent Structure Example 1 This embodiment provides a group of magnesium alloy vascular stent structures, the material of which is the BDM-6# material in the magnesium alloy material in embodiment 1, and the stent substrate 1 has different parameters. The structural parameters of the different groups are shown in Table 2. Here, the control group is an example of the magnesium alloy stent structure described in patent CN201520261612.

[0102] [Table 2]

[0103] Except for the different parameters shown in Table 2, the other parameters of each group of structures are the same, that is, the stent base 1 further includes a developing structure 4 connected to both ends of the stent base via connectors 3, the developing structure includes a developing point 41 made of platinum and a developing structure body 42, and a developing hole 43 is provided in the developing structure body 42. The diameter of the developing point 41 is 0.35 mm, the thickness is 0.14 mm, the compressed diameter of the stent base 1 is 1.3 mm, the expanded diameter is 3.0 mm, and the length is 13 mm.

[0104] Stent Example 1 This embodiment provides a degradable biomedical magnesium alloy drug-eluting vascular stent (shown in Figures 1-5), which includes a stent base 1, and a polymer intermediate layer 7, a polymer protective layer 6, and a drug coating layer 8 coated from the inside to the outside.

[0105] The stent base 1 uses the structure A in the first embodiment of the stent structure, and its material is the magnesium alloy material BDM-6# in the first embodiment.

[0106] The polymer interlayer 7 is sealed with magnesium fluoride, where the polymer is polyvinylidene fluoride and has a thickness of 1000 nm.

[0107] The polymer in the polymer protective layer 6 is polyvinylidene fluoride-hexafluoropropylene and has a thickness of 6 μm.

[0108] The components of the drug coating layer include a polymeric carrier and an active drug, the polymeric material of the polymeric carrier is PLLA, the active drug is arsenic trioxide and tacrolimus in a weight ratio of 1:1, and the weight ratio of the polymeric carrier to the active drug is 5:1, the content of arsenic trioxide is 5μg / mm, and the content of tacrolimus drug is 5μg / mm.

[0109] The fabrication of this degradable biomedical magnesium alloy drug eluting vascular stent includes:

[0110] (a) BDM-6# magnesium alloy bar was produced by the method described in Example 1 of magnesium alloy material, and then a magnesium alloy tube was produced by a tube drawing process. The magnesium alloy tube had an outer diameter of 3.0 mm, a wall thickness of 0.22 mm, and a length of 1 m.

[0111] (b) The magnesium alloy tube was fabricated into cut stents by laser engraving process.

[0112] (c) The laser-engraved stent was immersed in a cleaning solution for magnesium alloy stents and ultrasonically treated for 2 minutes to remove the cutting residue and oxide layer formed by laser engraving and attached to the surface. The cleaning solution for magnesium alloy stents was prepared from potassium dihydrogen phosphate, potassium fluoride, absolute ethanol and purified water, specifically, potassium dihydrogen phosphate 40g / L, potassium fluoride 20g / L, absolute ethanol 200ml / L, and the solvent was purified water.

[0113] (d) The cut stent after cleaning was clamped in a jig and immersed in a polishing solution for magnesium alloy stents to perform electrochemical polishing at a polishing temperature of 40° C., a polishing current of 1.2 A, and a polishing time of 80 s. The polishing solution for magnesium alloy stents was prepared from phosphoric acid, absolute ethanol, and purified water in a volume ratio of 1:1:1.

[0114] (e) A polymer interlayer was formed on the surface of the magnesium alloy stent substrate by ultrasonic spray coating process.

[0115] (f) The stent with the polymer intermediate layer applied on its surface was immersed in a fluoridation treatment solution and continuously stirred with a water bath shaker at a rotation speed of 80 r / min to fluoridize and seal the polymer undercoat. The fluoridation treatment solution was prepared from a hydrofluoric acid solution and a potassium fluoride solution, specifically, the concentration of the hydrofluoric acid solution was 40%, the concentration of the potassium fluoride solution was 5 mol / L, and the volume ratio of the hydrofluoric acid solution to the potassium fluoride solution was 100:30. The temperature of the fluoridation treatment solution was 75°C, and the treatment time was 300 min.

[0116] (g) A polymer protective layer was formed on the surface of the fluorinated polymer interlayer by an ultrasonic spray coating process.

[0117] (h) The stent coated with the polymer protective layer was placed vertically in a quartz tube and then transferred to a furnace chamber, which was then evacuated to a vacuum level of 1×10 -3 After the pressure exceeded 1 Pa, heating was started, the heat retention temperature was 120°C, the heat retention time was 2 h, the furnace was cooled to below 50°C, argon gas was introduced into the quartz tube, and the stent was taken out after the temperature had dropped to room temperature.

[0118] (i) A drug coating layer was formed on the surface of the stent protective coating layer by ultrasonic spray coating process.

[0119] (j) After drying, a degradable biomedical magnesium alloy drug-eluting vascular stent was obtained.

[0120] The ultrasonic spray coating is a method of coating the surface of a stent with a polymer using an ultrasonic spray coater. As shown in FIG. 28, the spray coating height was 30 mm, the air pressure was 11 KPa, and the rotation speed was 205 r / min.

[0121] Stent Example 2 This embodiment provides a degradable drug-eluting magnesium alloy vascular stent for biomedical use, which is a bare stent (without surface treatment and without any coating layer) consisting of only a stent base body 1.

[0122] The stent base 1 adopts structure A, which has high radial support and small maximum equivalent strain in the stent structure of Example 1, and is made of BDM-6# material, which is a magnesium alloy material in Example 1 and has good mechanical performance and corrosion resistance in both cases.

[0123] The fabrication of this degradable biomedical magnesium alloy drug eluting vascular stent includes:

[0124] (a) BDM-6# magnesium alloy bar was produced by the method described in Example 1 of magnesium alloy material, and then a magnesium alloy tube was produced by a tube drawing process. The magnesium alloy tube had an outer diameter of 3.0 mm, a wall thickness of 0.22 mm, and a length of 1 m.

[0125] (b) The magnesium alloy tube was fabricated into cut stents by laser engraving process.

[0126] (c) The laser-engraved stent was immersed in a cleaning solution for magnesium alloy stents and ultrasonically treated for 2 minutes to remove the cutting residue and oxide layer formed by laser engraving and attached to the surface. The cleaning solution for magnesium alloy stents was prepared from potassium dihydrogen phosphate, potassium fluoride, absolute ethanol and purified water, specifically, potassium dihydrogen phosphate 40g / L, potassium fluoride 20g / L, absolute ethanol 200ml / L, and the solvent was purified water.

[0127] (d) The cut stent after cleaning was clamped in a jig and immersed in a polishing solution for magnesium alloy stents to perform electrochemical polishing at a polishing temperature of 40° C., a polishing current of 1.2 A, and a polishing time of 80 s. The polishing solution for magnesium alloy stents was prepared from phosphoric acid, absolute ethanol, and purified water in a volume ratio of 1:1:1.

[0128] (e) After washing and drying, a degradable biomedical magnesium alloy drug-eluting vascular stent was obtained.

[0129] Stent Example 3 This embodiment provides a degradable biomedical magnesium alloy drug-eluting vascular stent, which comprises a stent substrate 1 and a magnesium fluoride protective layer.

[0130] The stent base 1 adopts structure A, which has high radial support and small maximum equivalent strain in the stent structure of Example 1, and is made of BDM-6# material, which is a magnesium alloy material in Example 1 and has good mechanical performance and corrosion resistance in both cases.

[0131] This magnesium fluoride protective layer is made of dense magnesium fluoride, uniformly covers the surface of the stent, and has a thickness of 1000 nm.

[0132] The fabrication of this degradable biomedical magnesium alloy drug eluting vascular stent includes:

[0133] (a) BDM-6# magnesium alloy bar was produced by the method described in Example 1 of magnesium alloy material, and then a magnesium alloy tube was produced by a tube drawing process. The magnesium alloy tube had an outer diameter of 3.0 mm, a wall thickness of 0.22 mm, and a length of 1 m.

[0134] (b) The magnesium alloy tube was fabricated into cut stents by laser engraving process.

[0135] (c) The laser-engraved stent was immersed in a cleaning solution for magnesium alloy stents and ultrasonically treated for 2 minutes to remove the cutting residue and oxide layer formed by laser engraving and attached to the surface. The cleaning solution for magnesium alloy stents was prepared from potassium dihydrogen phosphate, potassium fluoride, absolute ethanol and purified water, specifically, potassium dihydrogen phosphate 40g / L, potassium fluoride 20g / L, absolute ethanol 200ml / L, and the solvent was purified water.

[0136] (d) The cut stent after cleaning was clamped in a jig and immersed in a polishing solution for magnesium alloy stents to perform electrochemical polishing at a polishing temperature of 40° C., a polishing current of 1.2 A, and a polishing time of 80 s. The polishing solution for magnesium alloy stents was prepared from phosphoric acid, absolute ethanol, and purified water in a volume ratio of 1:1:1.

[0137] (e) The obtained stent base or stent base unit was immersed in a fluoridation treatment solution, and continuously stirred with a water bath shaker at a rotation speed of 80 r / min to perform a fluoridation treatment. The fluoridation treatment solution was prepared from a hydrofluoric acid solution and a potassium fluoride solution, and specifically, the concentration of the hydrofluoric acid solution was 40%, the concentration of the potassium fluoride solution was 5 mol / L, and the volume ratio of the hydrofluoric acid solution to the potassium fluoride solution was 100:30. The temperature of the fluoridation treatment solution was 75°C, and the treatment time was 300 min.

[0138] (f) After washing and drying, a degradable biomedical magnesium alloy drug-eluting vascular stent was obtained.

[0139] Stent Example 4 This embodiment provides a degradable biomedical magnesium alloy drug-eluting vascular stent, which includes a stent substrate 1, a magnesium fluoride intermediate layer, and a polymeric protective layer.

[0140] The stent base 1 adopts structure A, which has high radial support and small maximum equivalent strain in the stent structure of Example 1, and is made of BDM-6# material, which is a magnesium alloy material in Example 1 and has good mechanical performance and corrosion resistance in both cases.

[0141] This magnesium fluoride intermediate layer is made of dense magnesium fluoride, uniformly covers the surface of the stent, and has a thickness of 1000 nm.

[0142] The polymer in this polymeric protective layer is polymethylmethacrylate and has a thickness of 6 μm.

[0143] The fabrication of this degradable biomedical magnesium alloy drug eluting vascular stent includes:

[0144] (a) BDM-6# magnesium alloy bar was produced by the method described in Example 1 of magnesium alloy material, and then a magnesium alloy tube was produced by a tube drawing process. The magnesium alloy tube had an outer diameter of 3.0 mm, a wall thickness of 0.22 mm, and a length of 1 m.

[0145] (b) The magnesium alloy tube was fabricated into cut stents by laser engraving process.

[0146] (c) The laser-engraved stent was immersed in a cleaning solution for magnesium alloy stents and ultrasonically treated for 2 minutes to remove the cutting residue and oxide layer formed by laser engraving and attached to the surface. The cleaning solution for magnesium alloy stents was prepared from potassium dihydrogen phosphate, potassium fluoride, absolute ethanol and purified water, specifically, potassium dihydrogen phosphate 40g / L, potassium fluoride 20g / L, absolute ethanol 200ml / L, and the solvent was purified water.

[0147] (d) The cut stent after cleaning was clamped in a jig and immersed in a polishing solution for magnesium alloy stents to perform electrochemical polishing at a polishing temperature of 40° C., a polishing current of 1.2 A, and a polishing time of 80 s. The polishing solution for magnesium alloy stents was prepared from phosphoric acid, absolute ethanol, and purified water in a volume ratio of 1:1:1.

[0148] (e) The obtained stent was immersed in a fluoridation treatment solution, and was continuously stirred in a water bath shaker at a rotation speed of 80 r / min for fluoridation treatment. The fluoridation treatment solution was prepared from a hydrofluoric acid solution and a potassium fluoride solution, specifically, the concentration of the hydrofluoric acid solution was 40%, the concentration of the potassium fluoride solution was 5 mol / L, and the volume ratio of the hydrofluoric acid solution to the potassium fluoride solution was 100:30. The temperature of the fluoridation treatment solution was 75°C, and the treatment time was 300 min.

[0149] (f) A polymethyl methacrylate protective layer was formed on the surface of the magnesium fluoride protective layer by an ultrasonic spray coating process.

[0150] (j) After washing and drying, a degradable biomedical magnesium alloy drug-eluting vascular stent was obtained.

[0151] The ultrasonic spray coating was performed by coating the surface of the stent with a polymer using an ultrasonic spray coater. The spray height was 30 mm, the air pressure was 11 KPa, and the rotation speed was 205 r / min.

[0152] Test Example 1 Evaluation of mechanical and degradable properties of degradable magnesium alloy materials for biomedical use

[0153] Test material: Magnesium alloy material Example 1 Test method: Mechanical performance test was performed according to the test method described in "GB / T 228.1-2010 Metallic materials Tensile test Part 1: Room temperature test method". Cytotoxicity test was performed using the co-culture method.

[0154] Result explanation: The medical magnesium alloy material provided by the present invention can exhibit different mechanical performance and corrosion resistance performance under the conditions of different alloying element composition, and the alloying element ratio can be adjusted according to different implant requirements of different medical devices to control the degradation rate and mechanical performance of the substrate material.Preferably, the magnesium alloy substrate material applied to vascular stents requires high corrosion resistance performance, while the mechanical performance can be significantly improved at the application end by the design of the degradable vascular stent structure provided by the present invention.

[0155] The pull-out curves are shown in FIG. 6, the corrosion potentials are shown in FIG. 7, and the mechanical properties such as tensile strength are shown in Table 3 below.

[0156] [Table 3]

[0157] In addition, a cytotoxicity test was conducted on the magnesium alloy materials using the co-culture method. The relative proliferation rate of the materials reached 90% or more in all cases, and the cytotoxicity was first-class, meeting the characteristics of a biomaterial. The results are shown in Table 4.

[0158] [Table 4]

[0159] Test Example 2 Finite element analysis test of stent stress

[0160] Test Method: 1) Construction of a model: Modeling was performed at 1:1 according to the structural size of the stent base 1 of each group in Example 1 of the stent structure.

[0161] 2) Material properties: The expansion of the vascular stent is a large deformation process, and true stress and plastic strain should be used in the nonlinear finite element analysis process, so the test stress and test strain obtained in the material tensile test need to be converted into true stress and plastic strain. The stress / strain data of the BDM-6# material in Example 1 of the magnesium alloy material was converted into true stress / plastic strain and applied to the model. The conversion formula is as follows:

[0162]

number

[0163] 3) Grid division: The cell size is set to 0.016, the grid is divided into 6 layers in the thickness direction, and the 8-node hexahedral linear reduced integration unit C3D8R is selected. This unit provides relatively accurate solution results for displacement, and when there is torsional deformation in the grid (for example, the angle of the quad cell is large, much larger than 900), the analysis accuracy is not significantly affected, and shear locking is unlikely to occur under bending load.

[0164] 4) Boundary conditions: A cylindrical coordinate system was established at the central axial end of the model, axial and circumferential constraints were added to one end of the model to limit the axial rigid body displacement and end circumferential rotation displacement of the model, radial expansion displacement was added to the inner surface of the model, and radial compression gripping displacement was added to the outer surface.

[0165] 5) The stress / strain distribution of the stent structure was calculated, and the bearing reaction force was calculated to evaluate the radial support force of the stent.

[0166] 6) The comparison results are shown in Table 5 below. [Table 5]

[0167] Result explanation: The maximum equivalent strain indicates the stress concentration state during stent expansion, and the larger the value, the higher the degree of stress concentration, and the closer to the breaking elongation of the material, the easier it is to break. As shown in Table 5, the maximum equivalent strain of the control group is close to the breaking elongation of the material (15%), and the risk of breakage is quite high, but the support force is only 121 kPa. Compared with the control group, the stent structure A provided by the present invention significantly reduces the maximum equivalent strain of the stent and significantly improves the radial support force level of the stent. Compared with the control group, the stent structure B provided by the present invention has a lower maximum equivalent strain and can provide higher expansion safety under conditions where the requirements for radial support force are not high (e.g., small-sized cerebrovascular lesions). Compared with the control group, the stent structure C provided by the present invention maintains a radial support force close to that of the control group, while significantly reducing the maximum equivalent strain, improving the expansion safety of the stent. Compared with the control group, the stent structure D provided by the present invention has a maximum equivalent strain close to that of the control group and can provide higher radial support under conditions with a low risk of stent fracture (e.g., below-the-knee vascular lesions).

[0168] In ordinary vascular stents, for example, Patent CN201520261612 discloses an open-loop tube reticular magnesium alloy vascular stent (control group), in which the main support unit is in a "sine wave" form, and the support units are similarly connected by C-shaped arcs, but the "sine wave" main support unit has serious stress / strain concentration phenomenon on the inside of each wave arc in the stent expansion state. Calculation shows that, as shown in Figure 8, the structural stress concentration points are all in the inner center of the peak, and are prone to fracture when the stent is expanded. Because magnesium alloys have poor plasticity, in the actual application process, they need to first undergo a process of compression grip (outer diameter about 1.0-1.2 mm) and then expansion (outer diameter 2.5-4.0 mm), but serious stress concentration will lead to the expansion fracture of the stent. By increasing the height of the wave within the range of the structural parameters described in the patent, the overall stress / strain after the stent expansion can be reduced, but the radial support force is greatly reduced. Reducing the size of the stent substrate can also reduce the overall stress / strain after stent expansion, but along with the loss of radial support, a thin stent substrate increases the risk of corrosion fracture and is also detrimental to fatigue fracture resistance.

[0169] In contrast, the present invention focuses on optimizing the stress concentration points, and uses an innovative arc design to uniformly distribute the stress, while maintaining a sufficient expansion safety margin and ensuring a sufficient size to reduce the risk of structural destruction due to disintegration. Figures 9 and 10 show the stress distribution diagrams measured using the stent of Example 2 of the present invention as a test sample.

[0170] As can be seen from Figures 9 and 10, the stress / strain of the present invention is uniformly distributed on the beams on both sides, and the uniform distribution of stress / strain is realized without changing the width of the beam, which greatly improves the safety performance of the magnesium alloy stent.

[0171] Test Example 3 Stent coating layer evaluation

[0172] Test method: Observation using an electron microscope

[0173] Result explanation: FIG. 11 shows an electron microscope image of the polymer intermediate layer of the test sample of Example 1 of the stent of the present application, FIG. 12 shows an electron microscope image of the polymer intermediate layer sealed with magnesium fluoride, FIG. 13 shows an electron microscope image of the polymer protective layer spray-coated, FIG. 14 shows an electron microscope image after further annealing treatment, and FIG. 15 shows an electron microscope image of the drug coating layer applied.

[0174] Compared with the stent of the present application, the magnesium alloy stent that was only fluoridated (manufactured in Example 3 of the stent of the present application) is coated with a dense magnesium fluoride film layer on the surface. However, during the expansion process of the stent, stress fracture occurs in the magnesium fluoride film layer in the stress concentration area, cracks are formed on the surface, and the corrosion resistance of that area is significantly reduced. Furthermore, during the decomposition process of the stent, severe local corrosion occurs, and the film layer expands and breaks. An electron microscope image of this is shown in Figure 16.

[0175] Compared with the stent of the present application, the non-annealed polymer protective layer (manufactured in Example 4 of the stent of the present application) has insufficient bonding strength with the substrate, and due to the evaporation of the organic solvent during the spraying process, a large number of micropores are formed in the polymer protective layer, which is prone to damage to the membrane layer during stent expansion, as shown in the electron microscope image in Figure 17. Due to this damage, the region loses its ability to block body fluids or blood, and is unable to prevent ion exchange between the substrate and the implant environment, which leads to serious local corrosion in the early stage of decomposition. As a result, the loss of initial support force of the vascular stent due to the local corrosion becomes serious, leading to poor results such as the collapse of the vascular lumen.

[0176] Test Example 4 Evaluation of stent decomposition performance and support capacity under large deformation conditions in an in vitro simulated environment

[0177] Test method: The test was performed according to the fatigue durability test method described in "YY / T 0808-2010 Standard Test Method for In Vitro Pulsation Durability of Vascular Stents."

[0178] Result explanation: A degradable magnesium alloy bare stent (i.e., no coating layer on the stent substrate) was manufactured by the method of stent Example 2, and the obtained magnesium alloy bare stent degraded in 36 hours in a fatigue test after undergoing a large deformation process, and the stent was destroyed and lost its supporting force, as shown in Figure 18. This test shows that under near-physiological simulating conditions, the magnesium alloy bare stent without protective measures has a very fast decomposition rate due to the action of a large deformation process and continuous stress, which is much higher than the decomposition rate under normal environments (e.g., environments simulating immersion in body fluids).

[0179] A degradable biomedical magnesium alloy drug-eluting vascular stent was manufactured by the method of stent Example 3, and after decomposition for 3 days, the structure of the stent fell off over a large area, and the supporting force was lost, as shown in Figure 19. As is clear from the test, the inorganic salt (magnesium fluoride) film layer formed by surface treatment (e.g., fluorination) of the magnesium alloy stent can exert a certain corrosion resistance, but it cannot solve the problem of the film layer breakage at the stress concentration point, and the stent suffers a lot of structural destruction in the early stage of decomposition due to severe local corrosion.

[0180] A degradable biomedical magnesium alloy drug-eluting vascular stent was prepared according to the method of stent Example 4, and after 15 days of decomposition, the stent was broken in the axial direction, suffered severe stress corrosion, and lost its supporting force, as shown in Figure 20. It is clear from the test that the anti-corrosion ability of the magnesium alloy vascular stent has been improved to a certain extent by the multi-layer protection treatment of magnesium fluoride and polymethyl methacrylate protective layer, but the problem of the membrane layer being damaged under near-physiological conditions due to the large deformation process still remains unsolved, and severe local corrosion also occurs in the early stage of decomposition, and the stent structure falls off, losing supporting force, causing the collapse of the vascular lumen and other unfavorable results.

[0181] The degradable biomedical magnesium alloy drug-eluting vascular stent manufactured according to the method of Example 1 of the stent was degraded after 3 months, as shown in Figure 21. The degradation result shows that there was no drop-off or breakage in the entire stent structure, but only slight local corrosion was observed.

[0182] As can be seen from the test, the composite coating layer of the degradable biomedical magnesium alloy drug-eluting vascular stent provided by the present application can still exert an effective protective effect after undergoing a large deformation process under near-physiological conditions, providing effective protection in stress concentration areas, greatly improving the degradation time, reducing local corrosion areas, and allowing the supporting force of the stent to be maintained for three months.

[0183] Test Example 5 Animal testing evaluation

[0184] Test method: First, the animal model was pretreated, that is, at the vascular position where the stent was to be implanted, the blood vessel was dilated at an expansion ratio of 1.5 times the blood vessel diameter using a disposable balloon dilation catheter, causing some damage to the blood vessel, and a vascular embolism model was formed 4 weeks after pretreatment. Then, a degradable biomedical magnesium alloy drug-eluting vascular stent was implanted at the vascular embolization site, and the expansion ratio of the stent was 1.1 times the blood vessel diameter. The follow-up observations were performed one month and six months after the operation using angiography and intravascular OCT, respectively, and the intimal coverage of the stent, restenosis, and degradation were comprehensively evaluated.

[0185] The degradable biomedical magnesium alloy drug-eluting vascular stent manufactured entirely according to the method of Stent Example 1 was tested according to the test method described in Stent Test Example 5. The results show the following:

[0186] 1) As shown in Figure 22, the OCT photograph of the lumen of the planned implant site in a porcine blood vessel shows that the lumen is smooth.

[0187] 2) In the OCT image of the stenosis model after pretreatment of the planned implant site in a porcine blood vessel, as shown in Figure 23, the intima was rapidly proliferated, the lumen was lost, and the stenosis rate was nearly 50%, which meets the requirements of a vascular embolization model.

[0188] 3) After implanting the degradable biomedical magnesium alloy drug-eluting vascular stent provided by the present application, the OCT photograph shows that the stent has good adhesion, no fracture, and no lumen collapse, as shown in Figure 24. This result indicates that the supporting force of the magnesium alloy stent provided by the present application can meet the requirements.

[0189] 4) The results of the follow-up observation of the degradable magnesium alloy drug-eluting vascular stent for biomedical use provided by the present application one month after operation by OCT and DSA contrast are shown in Figure 25. The follow-up observation by contrast shows that the blood flows smoothly, there is no stenosis, and the development point is clearly visible, and the follow-up observation by OCT shows that the intima is completely covered, there is no intimal proliferation in the lumen, there is no inflammation, and the lumen loss rate is less than 5%. This result shows that the degradable magnesium alloy drug-eluting vascular stent for biomedical use provided by the present application can effectively control the degradation of the magnesium alloy substrate by its polymer intermediate layer 7 and polymer protective layer 6, and can realize rapid endothelialization, inhibit smooth muscle proliferation, and sufficiently suppress inflammation by its drug coating layer 8.

[0190] 5) The results of OCT observation 6 months after the operation of the degradable magnesium alloy drug-eluting vascular stent for biomedical use provided by the present application are shown in Figure 26, showing that there is still no proliferation in the vascular lumen, no inflammation, no loss of lumen, the decomposition of the stent has begun, and some trabeculae have become blurred. This result shows that the degradable magnesium alloy drug-eluting vascular stent for biomedical use provided by the present application has good therapeutic effect in the large animal coronary artery stenosis model test, effectively prolongs the stent decomposition time and the retention time of supporting force, has no inflammation, no proliferation, and has long-term safety.

[0191] 6) The developability of the degradable biomedical magnesium alloy drug-eluting vascular stent provided by the present application is such that the developed points at both ends of the stent are clearly visible under normal medical X-ray irradiation, as shown in Figure 27. The two developed points at each end are distributed at 90° in the circumferential direction, ensuring that the length and diameter parameters of the stent can be displayed at different angles.

Claims

1. 1. A degradable biomedical magnesium alloy comprising 3.0-6.0 wt% Gd, 2.5-5.5 wt% Y, 1.0-3.0 wt% Li, 0.3-1.0 wt% Zn, 0.2-1.0 wt% Zr, and the balance Mg, based on 100 wt% total weight of the magnesium alloy.

2. A degradable magnesium alloy drug-eluting vascular stent for biomedical use, comprising a stent base (1), a polymer intermediate layer (7) disposed on the stent base from the inside to the outside, a polymer protective layer (6), and a drug coating layer (8), A degradable magnesium alloy drug-eluting vascular stent for biomedical use, the material of the stent base (1) containing 3.0-6.0 wt % Gd, 2.5-5.5 wt % Y, 0.3-1.0 wt % Zn, 0.2-1.0 wt % Zr, and the remainder Mg, assuming the total weight of the stent to be 100 wt %.

3. 3. The degradable magnesium alloy drug-eluting vascular stent for biomedical use according to claim 2, wherein the stent base (1) is mainly composed of a plurality of annular supports (2), connectors (3) and end development structures (4), and each support (2) and the development structure (4) are connected by the connectors (3).

4. The degradable biomedical magnesium alloy drug-eluting vascular stent according to claim 3, wherein the support (2) is mainly composed of support units (5), each support unit (5) comprises one wavy rod (51), two wavy rod connecting sections (52) and one arc body (53), the wavy rod connecting sections (52) are installed on both ends of the wavy rod (51), the wavy rod connecting section (52) at one end is connected to one end of both ends of the arc body (53) of the same support unit, and the wavy rod connecting section (52) at the other end is connected to one end of the arc body (53) of the adjacent support unit, thereby forming an annular support (2).

5. The degradable biomedical magnesium alloy drug eluting vascular stent as claimed in claim 4, wherein the width of the wavy rod connecting section (52) is 0.01mm-0.05mm smaller than the width of the wavy rod.

6. The degradable biomedical magnesium alloy drug-eluting vascular stent as claimed in claim 5, wherein the width of the wavy rod (51) is 0.1mm-0.18mm, and the length of the wavy rod is 0.35mm-1.2mm.

7. 5. The degradable magnesium alloy drug-eluting vascular stent for biomedical use as claimed in claim 4, wherein the circular arc body (53) includes an outer circular arc (531) on the outside and an inner circular arc (532) on the inside, the centers of the circles on which the inner circular arc (532) and the outer circular arc (531) are located are both located on the symmetry axis of the two wavy rods (51) connected to the same circular arc body (53), but are not concentric, the center of the outer circular arc (531) is located closer to the apex of the arc than the center of the inner circular arc (532), and the distance between the inner circular arc (532) and the outer circular arc (531) is smallest at the connection part with the wavy rod connection section (52), gradually increases toward the apex of the circular arc body (53), and is largest at the symmetry axis.

8. The degradable biomedical magnesium alloy drug-eluting vascular stent as claimed in claim 7, wherein the diameter of the outer circular arc (531) is 0.24-0.82mm, the central angle is π / 2-3π / 2, the diameter of the inner circular arc (532) is 0.02-0.60mm, the central angle is π / 2-3π / 2, and the distance between the center of the outer circular arc and the center of the inner circular arc is 0.01-0.05mm.

9. The degradable biomedical magnesium alloy drug-eluting vascular stent according to claim 7, wherein the maximum distance between the inner circular arc (532) and the outer circular arc (531) is 0.01mm-0.05mm greater than the width of the wavy rod, and the minimum distance between the inner circular arc (532) and the outer circular arc (531) is 0.01mm-0.05mm smaller than the width of the wavy rod (51).

10. The degradable biomedical magnesium alloy drug-eluting vascular stent as claimed in claim 9, wherein the widths of both ends of the wavy rod connection section (52) are respectively the same as the width of the wavy rod (51) and the width of the end of the circular arc body (53), and the intermediate width gradually changes and transitions.

11. The degradable biomedical magnesium alloy drug eluting vascular stent according to any one of claims 2 to 10, wherein the compressed gripping diameter of the stent is 0.8mm-2.8mm, the expanded diameter is 2.0mm-8.0mm, and the length is 6mm-150mm.

12. The degradable magnesium alloy drug-eluting vascular stent for biomedical use according to any one of claims 2 to 10, wherein the polymer in the polymer protective layer (6) is polyvinylidene fluoride and its copolymer, and the thickness of the polymer protective layer (6) is 2μm-10μm.

13. The degradable magnesium alloy drug-eluting vascular stent for biomedical use as claimed in claim 12, wherein the polymer intermediate layer (7) is a polymer intermediate layer sealed with magnesium fluoride, the polymer in the polymer intermediate layer is one or a combination of a plurality of polymers selected from polyvinylidene fluoride and its copolymers, polymethyl methacrylate, and polybutyl methacrylate, and the thickness of the polymer intermediate layer is 100nm-2000nm.

14. The degradable magnesium alloy drug-eluting vascular stent for biomedical use as claimed in claim 12, wherein the vascular stent further comprises a drug coating layer (8) disposed on the outer surface of the polymer protective layer (6), the components of the drug coating layer comprise a polymer carrier and an active drug, and the active drug is a combination of tacrolimus and one selected from rapamycin and diarsenic trioxide.

15. The degradable magnesium alloy drug-eluting vascular stent for biomedical use according to claim 14, wherein the polymeric material of the polymeric carrier is one or a combination of more than one selected from polylactic acid, racemic polylactic acid, polyglycolic acid, polylactic acid-glycolic acid, polycaprolactone and polyhydroxy-butyric acid hydroxyvaleric acid copolyester.

16. The degradable biomedical magnesium alloy drug-eluting vascular stent according to claim 14, wherein the weight ratio of the polymer carrier to the active drug is 2:1-10:

1.

17. The degradable magnesium alloy drug-eluting vascular stent for biomedical use as claimed in claim 14, wherein the weight ratio of said arsenic trioxide or rapamycin to tacrolimus is 1:2-4:

1.

18. The degradable biomedical magnesium alloy drug-eluting vascular stent as claimed in claim 14, wherein the content of arsenic trioxide or rapamycin in the drug coating layer (8) is 2-20μg / mm, and the content of tacrolimus drug is 1-25μg / mm.

19. A method for producing a degradable magnesium alloy drug-eluting vascular stent for biomedical use according to any one of claims 2 to 18, comprising the steps of: (1) Processing of the stent base (1) (2) Coating of the polymer intermediate layer (7) (3) Coating of the polymer protective layer (6) (4) Application of drug coating layer (8)

20. The step (2) includes subjecting the polymer intermediate layer to a sealing treatment with magnesium fluoride, the sealing treatment with magnesium fluoride comprises immersing the stent substrate coated with the polymer intermediate layer in a fluoridation treatment solution and continuously stirring the solution in a water bath shaker at a rotation speed of 50 to 200 r / min; 20. The manufacturing method according to claim 19, wherein the fluoridation treatment solution is prepared by using a hydrofluoric acid solution and a potassium fluoride solution, the volume concentration of the hydrofluoric acid solution is 10-40%, the volume concentration of the potassium fluoride solution is 0.5-5 mol / L, the volume ratio of the hydrofluoric acid solution to the potassium fluoride solution is 100:5-100:50, the temperature of the fluoridation treatment solution is 18-85°C, and the treatment time is 30-600 min.

21. The step (3) includes annealing the applied polymer protective layer, 20. The method of claim 19, wherein the annealing treatment comprises heating the stent substrate coated with the polymer protective layer to 60-200°C under vacuum conditions, keeping the temperature for 1-10 hours, and then cooling the substrate to room temperature before removing the stent.

22. The vacuum level of the above vacuum conditions is 1×10 -3 The method according to claim 21, wherein the pressure is equal to or higher than Pa.

23. The method of claim 21, wherein the annealing treatment comprises heating the stent substrate coated with the polymer protective layer to 60-200°C under vacuum conditions, maintaining the temperature for 1-10 hours, naturally cooling to 50°C, introducing argon gas, further cooling to room temperature, and then removing the stent.

24. A method for evaluating a degradable biomedical magnesium alloy drug-eluting vascular stent in an animal model of vascular stenosis, comprising: First, a pretreatment of an animal model is performed by balloon expansion to form a vascular embolism model, and then a degradable biomedical magnesium alloy drug-eluting vascular stent according to any one of claims 2 to 18 is implanted, and then follow-up observations are performed at different time points after surgery using angiography and intravascular OCT to comprehensively evaluate the intimal coverage, restenosis and decomposition status of the stent.

Citation Information

Patent Citations

  • Modified medical magnesium alloy material and preparation method thereof

    CN111012955A

  • Graft with bioabsorbable support frame

    JP2009508644A

  • Magnesium alloy for bioabsorbable stents

    JP2014534841A

  • Stent excellent in corrosion resistance

    JP2015154925A

  • Fully degradable magnesium alloy and preparation method thereof

    US20190153570A1